Mass-customisation and self-reflective frameworks: early developments in New Zealand - Clayton , John (Research in Learning Technology, 2012)
Education has long been regarded as the foundation stone of national growth and international competitiveness. In the last three decades national educational reforms to improve access to higher education qualifications, individual higher education institutions’ aggressive national and international marketing initiatives and improved information and communication technology (ICT) systems and infrastructure have resulted in greatly increased participation in tertiary education. As a consequence of this wider participation, tertiary educators are now engaging with increased numbers of culturally and economically diverse learners in distributed ICT environments that they, the educators and learners, are often unfamiliar with. There is an expectation that these educators will be able to design learning modules to meet students’ multi-cultural needs, in a range of contexts, with no additional resources. In essence, it is expected that learners will participate in individually customised learning events at a cost similar to traditional delivery. This requires a fundamental shift in educators and learners conceptions on the provision of education. The purpose of this paper is to explore how the development and deployment of reflective frameworks, based on recognised international standards, can fully engage learners in mass-customised environments. First this article outlines the key building blocks required for reflective mass-customisation to occur. Second, it illustrates how this concept is being tentatively explored at a New Zealand institution. Finally, it recommends the areas of action for further research on the impact and effect of masscustomisation on learners, educators and institutions to be undertaken. Keywords: customisation; frameworks; self-reflection; New Zealand; assessment (Published: 30 August 2012) http://dx.doi.org/10.3402/rlt.v20i0.19187